2019
DOI: 10.1021/acs.chemmater.9b01395
|View full text |Cite
|
Sign up to set email alerts
|

Role of Surface Reduction in the Formation of Traps in n-Doped II–VI Semiconductor Nanocrystals: How to Charge without Reducing the Surface

Abstract: The efficiency of nanocrystal (NC)-based devices is often limited by the presence of surface states that lead to localized energy levels in the bandgap. Yet, a complete understanding of the nature of these traps remains challenging. Although theoretical modeling has greatly improved our comprehension of the NC surface, several experimental studies suggest the existence of metal-based traps that have not yet been found with theoretical methods. Since there are indications that these metal-based traps form in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
133
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(152 citation statements)
references
References 62 publications
15
133
0
4
Order By: Relevance
“…Indeed, the standard reduction potential of Zn 2+ is 0.36 V more negative than of Cd 2+ , 62 and our recent DFT calculation shows an improved electrochemical stability of ZnS surfaces compared to CdSe and CdS surfaces. 32…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the standard reduction potential of Zn 2+ is 0.36 V more negative than of Cd 2+ , 62 and our recent DFT calculation shows an improved electrochemical stability of ZnS surfaces compared to CdSe and CdS surfaces. 32…”
Section: Resultsmentioning
confidence: 99%
“…Such reactions have been observed and discussed before and have sometimes been assigned to the reduction of surface Cd 2+ to Cd 0 . 4750 However, the occurrence and nature of such surface electrochemical reactions, and their potential reversibility, are largely unknown.…”
Section: Resultsmentioning
confidence: 99%
“…From the electronic structure point-of-view, even a reduction of few atoms due to charging (e.g., Cd 0 in a cadmium chalcogenide) has signicant inuence as it forms a trap. 151 On a larger scale, an ammonia electrosynthesis catalyst was prepared by reduction of iron oxyhydroxide to form a core-shell aFe-Fe 3 O 4 hybrid by annealing under a reducing H 2 (g) environment. 152 Another interesting related example is the formation of a bimetallic thin layer in a HNS: Peng and co-workers have shown that for Pt/ Fe 3 O 4 core/shell triangular nanoprisms, an interfacial ironplatinum layer is formed.…”
Section: Colloidal Routes To Form M/sc Interfacesmentioning
confidence: 99%